The importance of antibiotic residues presence detection in milk - Dubravka Samaržija; Neven Antunac (Mljekarstvo)
Antibiotic residues are the most present inhibitory substances in milkhaving undesirable effect on human health, technological characteristics and the quality of milk and dairy products. In order to protect consumer's health and to ensure high quality milk production, European Union (EU) regulation 2377/90 sets a maximum permitted levels for antibiotic residues in milk. Although the presence of antibiotic residues in milk can be due to animal diseases treatment, and in the case of milking animals, they are mostly present after mastitis treatment. The aim of this work is to stress the importance of the continuous control on antibiotic residues presence in milk, due to the role that milk and dairy products have in human nutrition. In this paper, different groups of antibiotics, mechanisms of theirs action, mistakes occurring in dairy products manufacture as well as the methods for theirs detection are described.